التصميم اإلنشائي لقصر الثقافة في مدينة الخليل - بدر, بهاء; النتشه, فواز; شويكي, منتصر; الحلواني, محمد (جامعة بوليتكنك فلسطين - مباني, 2014)
The main idea of this project is to prepare all structural design and executive details for The Hebron Culture Palace. The palace consists of several buildings and architectural design features of the project that shows the Arab and Islamic culture in addition to that is summarizing the Palestinian reality under Israeli occupation, by presence of a wall separating the buildings from each other as the "separation wall". The importance of the project to the need to have a building like that in the city of Hebron, there are many events that need a place to take care of the movement of cultural, lectures, plays, ceremonies, etc. The importance of construction lies in the diversity of structural elements in different buildings in addition to changing levels in the building. The project will include the study of structural detail to identify and analyze the elements of construction and different loads expected and then the structural design of the elements and the preparation of drawings of the elements construction and will be designed - God willing - based on the requirements of the ( ACI_318 code ) and use some structural design programs.
no of pages 135, 13971, مباني 6/2014, in the store
Keywords: التصاميم الانشائية; الابنية الثقافية